Faktor Faktor Yang Berhubungan Dengan Tingkat Kecemasan Ibu Pada Masa Menopause Di Desa Krueng Meuriam Kecamatan Tangse Kabupaten Pidie - Ayu Mukarramah; Fahmi Ichwansyah; Ghazali Amin (CV. Pusdikra Mitra Jaya, 2022)
In 2020, Indonesia only reached 14 million menopausal women or 7.4% of the total population. When a woman has entered the menopause stage, the levels of estrogen and progesterone gradually drop so that they also affect other hormones. This condition is closely related to women's anxiety during menopause. The purpose of this study was to determine the factors associated with maternal anxiety levels during menopause in Krueng Meuriam Village, Tangse District, Pidie Regency in 2021. Methods: This research is an analytic with a cross sectional approach. The population in this study were 145 postmenopausal women in Krueng Meuriam Village, Tangse District, Pidie Regency in 2021. Sampling in this study was carried out by proportional sampling by determining the number of samples using the Slovin formula so that a sample of 60 samples was obtained. Data collection was carried out from December 02 - 08 by using a questionnaire through interviews. Data analysis using Chi-Square test with SPSS 21 . program. Results: The results showed that 40% of respondents who experienced normal anxiety during menopause, 56.7% of respondents with good knowledge, 55% of respondents with positive attitudes, 56.7% of respondents who had family support, and 56.7% of respondents who experienced mild physical changes by 45%.. Conclusion: Based on the results of the study, it was concluded that the results of bivariate research with chi-square test showed that there was a relationship between knowledge p = 0.021, there was a relationship betwee attitudes p = 0.032, there was a relationship between family support p = 0.004, and there was a relationship between physical changes p = 0.040 with maternal anxiety during menopause.